ANALISIS NARATIF TERHADAP LUKAS 15:11-32: KAJIAN INTERVENSIN KRISIS JAMES DAN GILLILAND - Djarang, Gledis; Makiengung, Erci Alicia; Tamamilang, Inkan S (DELAHA: Journal of Theological Sciences, 2025)
This article intends to analyze more deeply regarding the continued handling of the crisis experienced by the youngest child in the biblical text entitled "The Parable of the Prodigal Son", namely by analyzing it from a different perspective in a more complex pastoral counseling context. The aim of this research is to look at the handling of the crisis in the text of Luke 15:11-32 as well as follow-up actions towards the crisis experienced using a narrative hermeneutic approach to see the formation of trauma and the complex process of crisis occurrence, then analyze the psychological and emotional crisis that is formed by studying it using James and Gilliland's crisis intervention theory.